Grammar learning strategies among adult learners / Razalina Ismail - Ismail, Razalina (2010)
This study attempts to investigate the use of grammar learning strategies on 56 participants from UiTM Dungun, Terengganu. There are five grammar learning strategies focused in this study namely the memory strategies, cognitive strategies, compensation strategies, metacognitive strategies and social strategies. The objective of this study is to find out whether adult learners are using the grammar learning strategies and which grammar learning strategy is most commonly used by the adult learners. Other than that this study was also intended to investigate the differences between teachers and non teachers in the use of grammar learning strategies and also the differences between the gender of the adult learners in the use of grammar leaning strategy.